Chemical Composition and Constituent Value of Selected Soybean (Glycine max (L.) Merrill) Cultivars Grown in Turkey - Gaytancioglu, Okan; Tasan, Murat; Gecgel, Umit; Arslan, Dilaver (Asian Journal of Chemistry, 2010)
The aim of this study was to determine and to compare the seed chemical characteristics and constituent value of selected soybean (Glycine max (L.) Merrill) cultivars which were grown in the experimental areas of the Black-Sea Agricultural Research Institute, Samsun, Turkey. Moisture, crude protein, crude oil and ash contents and fatty acid compositions in the seeds of 20 soybean cultivars were determined. According to the findings of the research, the major fatty acids were linoleic (C18:2) and oleic (C18:1) acids, whose contents were in the ranges 51.76-56.76 % and 18.84- 26.35 %, respectively. All of the cultivars contained linolenic (C18:3) acid, with values ranging from 6.01 to 8.32 %. Palmitic (C16:0) and stearic (C18:0) acids were the main saturated fatty acids, 10.14-12.19 and 3.49-4.67 %, respectively. Small amounts of C14:0, C16:1, C17:0, C17:1, C20:0, C20:1, C22:0, C24:0 and C24:1 were determined (< 1 %). The crude oil contents of the soybean cultivars were varied from 17.28 to 20.71 % of the weight of whole seed. The important chemical component of the cultivars was the crude protein, which ranged from 35.02 to 39.11 %, as whole seed basis. Moisture and total ash contents were in the ranges 6.05-8.62 and 3.62-5.46 %, respectively.